Secure wireless transmission without keys : a physical layer approach - Tan, Kwan Hong (2018)
Wireless network is widely used in all kind of communication exchange in our daily life today. With so much information exchange happening around the world, the security of these information during the transmission process becomes a critical issue in wireless applications. Especially in military applications. And with adversaries’ advancing computation techniques to disrupt information exchange creates a greater need to improve and seek for techniques to optimize transmission secrecy. This report will provide an insight on the need for physical layer security in today’s highly connected systems and explore secure communication without using cryptographic protocols. MATLAB® functions is used to simulate several concepts of wireless communication network and existing secure wireless transmission scheme.